2015
DOI: 10.1021/acscatal.5b01667
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Lanthanum-Based Perovskite Oxides for Catalysis

Abstract: There is a need to reduce the use of noble metal elementsespecially in the field of catalysis, where noble metals are ubiquitously applied. To this end, perovskite oxides, an important class of mixed oxide, have been attracting increasing attention for decades as potential replacements. Benefiting from the extraordinary tunability of their compositions and structures, perovskite oxides can be rationally tailored and equipped with targeted physical and chemical propertiesfor example, redox behavior, oxygen mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
287
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(293 citation statements)
references
References 141 publications
3
287
0
3
Order By: Relevance
“…Very similar E a values of 113.0 kJ·mol −1 , 112.2 kJ·mol −1 and 95.6 kJ·mol −1 ,that are consistent with the literature data [34], were obtained for LaFeO 3 , La 0.8 Sr 0.2 FeO 3 and La 0.6 Sr 0.4 FeO 3 catalysts respectively. As expected, apparent activation energies show a slight dependence on the A-site ions with the partial Sr-substitution for La [35] because B-site transition metals, such as Fe, provide redox active site to facilitate catalytic reactions [36].…”
Section: -6supporting
confidence: 72%
“…Very similar E a values of 113.0 kJ·mol −1 , 112.2 kJ·mol −1 and 95.6 kJ·mol −1 ,that are consistent with the literature data [34], were obtained for LaFeO 3 , La 0.8 Sr 0.2 FeO 3 and La 0.6 Sr 0.4 FeO 3 catalysts respectively. As expected, apparent activation energies show a slight dependence on the A-site ions with the partial Sr-substitution for La [35] because B-site transition metals, such as Fe, provide redox active site to facilitate catalytic reactions [36].…”
Section: -6supporting
confidence: 72%
“…The perovskite structure ABO3−δ has been chosen for many systematic studies of catalytic activity [25,[46][47][48][49][50], including oxygen reduction and evolution (i.e., oxygen electrocatalysis) [14,22,[25][26][27][28][51][52][53][54][55]. The key idea of this section is a demonstration of both intentional and unintentional effects of chemical substitution or changes in stoichiometry on the activity for oxygen reduction ( Figure 2).…”
Section: Effect Of Chemical Substitution On Activitymentioning
confidence: 99%
“…Systematic empirical studies of the ORR on oxides have been performed since the 1970s (Table 1), where highly active oxides were characterized by amphoteric metallic conduction [17,21], sigma bands [17] with an occupation near unity of e g orbitals [22], high covalence [22], and paramagnetism [23,24] fostering a specific ('side-on') configuration of the likewise paramagnetic oxygen molecule on the surface. Oxides with perovskite or closely related structures played an important role in the discovery of these insights because their physicochemical properties can be systematically tuned [14,22,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…36,37 These materials have also been shown to represent important replacements for platinum in electrolysis and fuel cells. 34,38 We conducted preliminary tests using these commercially available materials as cathode materials for RFCBs and found that RuO 2 showed a higher cathode performance than IrO 2 .…”
Section: Resultsmentioning
confidence: 99%